A study of IoT platforms and ecosystems - Vuorenmaa, Jarno (fi=Turun yliopisto|en=University of Turku|, 2016)
The Internet of Things promises novel applications, new markets, and improvements to business processes. This thesis discusses related challenges from technical and economic perspective. Despite the rapid development of technologies enabling the IoT, there are still crucial technological issues to be solved. These are for example scalability, heterogeneity, and security. Furthermore, the business world is not ready to invest into the IoT as it lacks suitable business models, success stories, and comprehensive set of economically succeeded IoT solutions. This thesis studies creation of IoT business models and ecosystems. IoT platforms are seen as facilitators for challenges and ecosystems raising within the IoT. An ecosystem evolves around common assets which can be exploited by members of the ecosystem. An advantage of an ecosystem from the IoT perspective is that it unites experts to solve challenges together. This thesis discusses what components a comprehensive IoT platform is built on. An IoT platform is seen as a central component of IoT solutions as it both facilitates challenges and unites experts. This thesis discusses potentiality to create an ecosystem around an IoT platform. This is demonstrated via a prototype which bases on Amazon Web Services’ IoT platform. The prototype contains several decoupled components, which can be seen as individual pieces of software made by a member of the ecosystem. These components have necessary domain specific logic, while the platform handles communication between the components, secures connections and offers database solution.